Pelatihan Karyawan Pada Pt Vinix Seven Aurum - Siti Aliyah; Tini Kartini (MAMEN: Jurnal Manajemen, 2026)
Employee training is a critical factor in improving work performance, productivity, and competence within a company. At PT Vinix Seven Aurum, the implementation of employee training faces challenges related to the training methods and the clarity of training objectives. Despite the application of On The Job Training (OJT), including coaching, direct supervision, and apprenticeship, the training process remains informal, unstructured, and partially conducted online, which affects the consistency of guidance and the understanding of training materials. This study aims to analyze the implementation of internal and external training programs, evaluate employee participation, and assess the role of mentors in supporting effective learning. A descriptive qualitative approach was applied, with data collected through observation, interviews, discussion, analysis, and implementation of findings. The results indicate that while instructors and training materials are considered adequate, 25% of employees perceive that training targets are not clearly defined, and 20% consider online training methods less effective. Recommendations include structuring OJT methods according to job characteristics and employee experience, assigning mentors for consistent guidance, and defining measurable training objectives documented in training modules or syllabi. By applying these improvements, PT Vinix Seven Aurum can enhance employee technical skills, increase training effectiveness, and strengthen overall human resource competence to support organizational goals.